Deformation and Failure Mechanism of Surrounding Rock in Mining-Influenced Roadway and the Control Technology. (19th April 2021) - Feng, Jicheng; Yin, Shuaifeng; Cheng, Zhiheng; Shi, Jianjun; Shi, Haoyu; Xu, Haitao; Guo, Shuying
Abstract : Aiming at the problem of surrounding rock deformation and failure of mining roadway and its control, a mechanical model of the circular roadway under the mining environment is established, and the implicit equation of the plastic zone boundary is derived. By analyzing the morphologic evolution law of the surrounding rock plastic zone in the mining roadway, the key factors affecting the morphologic change of the plastic zone are obtained, that is, the magnitude and direction of principal stress. The influence law of the magnitude and direction of principal stress on the plastic zone of the mining roadway is analyzed by using numerical simulation software, and the deformation and failure mechanism of surrounding rock of the mining roadway is revealed. The results showed that the size and morphology of the plastic zone were closely related to the confining pressure ratio ( η ). Taking the boundary of η valuing 1, the larger or smaller η value was, the more serious the deformation and failure of surrounding rock would be; the morphology of the plastic zone changed with the deflection of the principal stress, with the location of the maximum plastic zone influenced by the principal stress direction. For the surrounding rock control in the mining-influenced roadway, it is advised to take the following methods: firstly, it is necessary to consider how to reduce or remove the influence of mining on surrounding rock, improve the stress environment of surrounding rock, and reduce the failure depth of the plastic zone, so as to better maintain the roadway. Secondly, in view of the deformation and failure characteristics of the mining roadway, the fractional support method of "yielding first and then resisting" should be adopted, which applies the cable supplement support after mining instead of the one-off high-strength support during roadway excavation, so as to control the malignant expansion of the surrounding rock plastic zone and prevent roof falling accidents.